THE MENDING OF A FRACTURED SELF. ON THE SELF AS A PRODUCED AND SUSTAINED ENTITY - HALL, Sterling (Studia Universitatis Babeș-Bolyai Philosophia, 2021)
Experientially, we often have a sense of self which is relatively constant across moments in one’s personal timeline. There are instances where this sense of self fractures, though, and self-identity becomes difficult to sustain. This essay argues that such fracturing is the result of an interruption in a process of self-narrativization—an interruption which can be mended, at least partially, through creative and communal practices which allow for the possibility of recreating narratives at the site of their failure—and explores the meaning of this fracturing and mending process in terms of colonial violence as an example of a fracturing situation.